2021
DOI: 10.3390/neurolint14010003
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré Syndrome in the COVID-19 Pandemic

Abstract: There have been several reported cases of severe acute respiratory syndrome (SARS-CoV-2) infection that were associated with an increased incidence of neurological manifestations, including Guillain–Barré syndrome (GBS). This review aims to present information on the reports of GBS associated with coronavirus disease 2019 (COVID-19) infection. Our review is retrospective work examining articles published from the 1 April 2020 to the 8 May 2021 in the English language. We used the diagnostic criteria and classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 106 publications
1
11
0
Order By: Relevance
“…Based on the diagnostic criteria of neuropathy that were mentioned in Table 1 previously and the normal references mentioned in Table 2 , it was found that among the COVID-19 group, GBS was the most common type of inflammatory polyneuropathy, and all the cases were acute inflammatory demyelinating polyneuropathy (AIDP) except one, which was reported as acute motor-sensory axonal neuropathy (AMSAN), and the majority of patients had mixed motor and sensory involvement (Table 5 ). These results are also consistent with those of Tawakul et al in 2022; they found that AIDP was the most common type, and classic sensorimotor GBS was the commonest type and accounted for 56.19% of all cases, while pure motor GBS accounted for 17.14% of patients [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Based on the diagnostic criteria of neuropathy that were mentioned in Table 1 previously and the normal references mentioned in Table 2 , it was found that among the COVID-19 group, GBS was the most common type of inflammatory polyneuropathy, and all the cases were acute inflammatory demyelinating polyneuropathy (AIDP) except one, which was reported as acute motor-sensory axonal neuropathy (AMSAN), and the majority of patients had mixed motor and sensory involvement (Table 5 ). These results are also consistent with those of Tawakul et al in 2022; they found that AIDP was the most common type, and classic sensorimotor GBS was the commonest type and accounted for 56.19% of all cases, while pure motor GBS accounted for 17.14% of patients [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Also, our findings are similar to those of Zuberbühler et al, who reported in 2021 that male cases accounted for 64.6% of all cases, with a mean age of 56.4 years [ 23 ]. Similarly, according to the most recent published literature by Tawakul et al in 2022, the average age of the patients was 56.6 years, the most common gender was male (59.05% of cases), and only 18.10% of patients had no previous medical history [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations